2010
DOI: 10.1002/app.32033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterizations, and mechanical properties of structurally modified poly(vinyl alcohol)

Abstract: Poly(vinyl alcohol) (PVA) was structurally modified with two different types of chemicals under nitrogen atmosphere in the presence of Sb 2 O 3 as a catalyst at 80 C in an aqueous medium. An FTIR and NMR spectrum confirmed the structural modification of PVA. DSC and TGA counseled the thermal properties of structurally modified PVA. Urea modified PVA exhibited higher mechanical strength than the pristine PVA. The FTIR-relative intensities of olefin formation and ketone formation were increased with the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…The FTIR‐RI confirmed the decrease in crystallinity of PVA through the formation of ketone and olefin groups. This is in accordance with our earlier communications 36–38…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The FTIR‐RI confirmed the decrease in crystallinity of PVA through the formation of ketone and olefin groups. This is in accordance with our earlier communications 36–38…”
Section: Resultssupporting
confidence: 94%
“…The T d.w of PVA at 2 and 10% weight loading of NiO is 95.8 and 82.1°C respectively. This indicated that while increasing the % weight of NiO, the amount of physisorbed water molecules by PVA was drastically reduced i.e., the hydrophobicity is increased with the increase of NiO content, due to its nano size 36, 37. The decrease in water content with the increase of NiO content was already supported by the TGA of PVA/NiO systems [Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…For PLFM, the O-H stretching vibration absorption peak of hydroxyl groups is found at 3440 cm -1 , the double alcohol vibration absorption peak at 1700 to 1720 cm -1 , the stretching vibration absorption peak of the secondary alcohol at 1069 cm -1 , and the C-O-C-O-C stretching vibration peak at 1242 and 1018 cm -1 . The spectrum of PLCFM was similar to that of PLFM, except that the increase in the intensity of the absorption peak at 1180 to 1080 cm -1 , which was mostly due to C-O-Si and Si-O-Si, appeared during the reaction process (Anbarasan et al 2010). At the same time, the primary alcohol shock absorption peak at 1012 cm -1 was weakened because of the increased primary alcohol content in the reaction.…”
Section: Fig 4 Condensation Reaction Of Plfm and Teos Hydrolysismentioning
confidence: 55%
“…The structure of PVA was modified with 4‐maleiidohenylisocyanate and its thermal and mechanical properties were tested . Similarly, the structure of PVA was modified with chitosan, rifambin, glycidylmethacrylate, glycoside, N ‐alkyl‐substituted carbamates, 3‐diethylaminopropylamine, succinimide, propargylamine, poly(ɛ‐caprolactone), diethylchlorophosphate, soy bean oil triglycerides, and natural rubber latex for various end user applications. In 2010, Wang and Hsieh modified the structure of PVA with PEG diacrylchloride.…”
Section: Introductionmentioning
confidence: 99%